Assessing Artificial Intelligence (AI) Literacy and Readiness in Thailand’s Workforce: Challenges and Opportunities for Digital Transformation - Kaewsawad, Vachirawit; Duda, Jerzy (Science & Technology Asia, 2025)
As this paper seeks to examine how Thailand’s workforce readiness for AI technologies can be influenced by AI literacy, anxiety, and acceptance factors, the researcher has conducted an online survey of 318 respondents across multiple Thai industries as well as employing the Structural Equation Modeling or SEM to analyze the relationship between these factors. The modified Unified Theory of Acceptance and Use of Technology (UTAUT) framework has also been implemented and revealed that AI literacy can significantly reduce anxiety (𝛽 = -0.892, 𝑝 < 0.001) while the effort expectancy strongly influences the AI acceptance (𝛽 = 0.370, 𝑝 < 0.001). This suggests that there is a psychological barrier that should be addressed alongside technical skills improvement. The study has also found that AI literacy can positively influence performance expectancy (𝛽 = 0.262, 𝑝 < 0.001) and effort expectancy (𝛽 = 0.327, 𝑝 < 0.001) which enhances AI’s perceived usefulness and ease of use. The author’s model validates ten of the fourteen hypotheses, confirming that the facilitating conditions can significantly impact AI’s acceptance while social influences show positive yet non-significant effects. These findings altogether provided actionable insights for policymakers and organizations to develop and adopt the targeted interventions that can enhance both AI competency and a more optimistic environment towards integration of AI technologies in Thailand’s workforce.